Selective adipocyte loss of Angiopoietin-2 prompts female-specific obesity and metabolic syndrome - Bin Ni; Shanshan Chen; Kathleen A. Ryan; Michael L. Maitland; Jared S. Farrar; Martin Witzenrath; Birgitt Gubier; Cindy Serdjebi; Karine Bertotti; Rui Wang; Fadi N. Salloum; Luigi Marino; et al. (Molecular Metabolism, 2022)
Thermogenic fat differentiation and function can be promoted through multiple pathways, resulting in a common cell phenotype characterized by the expression of Uncoupling Protein-1 and the ability to dissipate energy, but local and systemic stimuli are necessary to promote adequate thermogenic fat vascularization, which is a precondition for the transport of substrate and the dissipation of heat. Angiopoietin-2 is an important driver of vascularization, and its transcription is in part promoted by estrogen signaling. In this study we demonstrate that adipose tissue-specific knock out of Angiopoietin-2 causes a female-specific reduced thermogenic fat differentiation and function, resulting in obesity and impaired glucose tolerance with end-organ features consistent with metabolic syndrome. In humans, angiopoietin-2 levels are higher in females than in males, and are inversely correlated with adiposity and age more strongly in pre-menopause when compared to post-menopause. Collectively, these data indicate a novel and important role for estrogen-mediated Angiopoietin-2 adipose tissue production in the protection against calorie overload in females, and potentially in the development of postmenopausal weight gain.